Communion Tokens of the Established Church of Scotland - Sixteenth, Seventeenth, and Eighteenth Centuries (Proceedings of the Society of Antiquaries of Scotland, 1907)
An exploration of the role of communion tokens in Scotland. It describes their use in Scottish religious practice, how the markings on tokens changed over time and how the tokens were made. The paper concludes with an alphabetical list of list of tokens and their descriptions, followed by illustrations of over 1000 tokens and their place of origin (where known).